Piecing together a new mosaic: Gravettian lithic resources and economic territories in the Western Pyrenees - Calvo, Aitor; Arrizabalaga, Alvaro (Archaeological and Anthropological Sciences, 2020)
To palliate the current scarcity of information about lithic raw materials in the Western Pyrenees during the Gravettian, the study of ten assemblages has explored the flint procurement patterns and economic organisation of the territory. The study was based on the macro- and microscopic analysis of the different lithic remains. A wide range of flint varieties were used, including some excellent rocks for knapping and others of poorer quality. This diversified catchment pattern was defined by the criteria of quality and suitability for reduction. Although procurement took place mostly at the primary outcrops, there is some evidence of limited acquisition in secondary deposits. Within the economic territory of the Western Pyrenees, divergences in the connections between the outcrops on one side of the mountains and the archaeological sites on the other may indicate different territorial or economic roles for each side. In general terms, the northern side may have been more residential with more stable habitation, while the southern side was linked with logistic tasks and more seasonal occupation. The economic connections between this territory and surrounding areas revealed by the lithic resources are the reflection of inter-group contacts and an economic mosaic imbricated with a cultural or symbolic one.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Economy; Gravettian; Lithic industry; Raw materials; Territory; Upper Palaeolithic